Association between retinal markers and cognition in older adults: a systematic review. Issue 6 (21st June 2022) - Jeevakumar, Varshanie; Sefton, Rebekah; Chan, Joyce; Gopinath, Bamini; Liew, Gerald; Shah, Tejal M; Siette, Joyce
Abstract : Objectives: To appraise the existing literature reporting an association between retinal markers and cognitive impairment in adults aged 65 years and over and to provide directions for future use of retinal scanning as a potential tool for dementia diagnosis. Design: Systematic review of peer-reviewed empirical articles investigating the association of retinal markers in assessing cognitive impairment. Data sources: Three electronic databases, Medline, PsycINFO and EMBASE were searched from inception until March 2022. Eligibility criteria: All empirical articles in English investigating the association between retinal markers and cognition in humans aged ≥65 years using various retinal scanning methodologies were included. Studies with no explicit evaluation of retinal scanning and cognitive outcomes were excluded. Risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies tool. Data extraction and synthesis: Data extraction was conducted by two authors (VJ, RS) and reviewed by another author (JS). Results were synthesised and described narratively. Results: Sixty-seven eligible studies examining 6815 older adults were included. Majority of studies were cross-sectional (n=60; 89.6%). Optical coherence tomography (OCT) was the most commonly used retinal scanning methodology to measure the thickness of retinal nerve fibre layer, the ganglion cell complex, choroid and macula. 51.1% of cross-sectional studies using OCT reported an association between the thinning of at least one retinal parameter and poor cognition. Longitudinal studies (n=6) using OCT also mostly identified significant reductions in retinal nerve fibre layer thickness with cognitive decline. Study quality was overall moderate. Conclusion: Retinal nerve fibre layer thickness is linked with cognitive performance and therefore may have the potential to detect cognitive impairment in older adults. Further longitudinal studies are required to validate our synthesis and understand underlying mechanisms before recommending implementation of OCT as a dementia screening tool in clinical practice. PROSPERO registration number: CRD42020176757.